2017
DOI: 10.3201/eid2303.160377
|View full text |Cite
|
Sign up to set email alerts
|

Autochthonous Outbreak and Expansion of Canine Visceral Leishmaniasis, Uruguay

Abstract: We report an outbreak of canine visceral leishmaniasis in Uruguay. Blood specimens from 11/45 dogs tested positive for Leishmania spp. Specimens of Lutzomyia longipalpis sand flies were captured; typing revealed Leishmania infantum. Our findings document an expansion of visceral leishmaniasis to southern South America and risk for vectorborne transmission to humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 9 publications
0
30
0
Order By: Relevance
“…An increase in cases of VL has been observed in the Southern Cone of Latin America, due to the great endemicity of canine reservoirs in urban and peri-urban areas [ 5 , 6 ]. A displacement to new areas free of VL cases has also been detected, like in Uruguay, where the first case of canine Leishmaniasis was reported in October 2015, with an initial confirmed canine prevalence of 18% in a few months [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…An increase in cases of VL has been observed in the Southern Cone of Latin America, due to the great endemicity of canine reservoirs in urban and peri-urban areas [ 5 , 6 ]. A displacement to new areas free of VL cases has also been detected, like in Uruguay, where the first case of canine Leishmaniasis was reported in October 2015, with an initial confirmed canine prevalence of 18% in a few months [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Visceral leishmaniasis has been investigated in southern Brazil for more than a decade. There are currently humans and dogs case records in the three border region (Brazil, Argentina and Uruguay) (Salomón et al, ; Salomon et al, ; Satragno et al, ). We have found Leishmania infection in equine peripheral blood in sites with CVL, inferring the possibility that animals residing in endemic CVL areas are at risk of being infected.…”
Section: Resultsmentioning
confidence: 99%
“…Leishmania spp. infection in domestic reservoirs of Uruguaiana city represents a higher infection rate than that found in a survey in Uruguay (22%) with L. infantum(Satragno & Faral- Tello, 2017). The vectors have food preference for dogs and humans(Macedo-Silva et al, 2014); however, other mammalian species, in-…”
mentioning
confidence: 83%
“…In Uruguay, a survey in Salto, a city on the border with Argentina, found 22% seroprevalence for Leishmania spp. (Satragno et al 2017) [EB1]. Studies of the seroprevalence of CVL in Mexico, Venezuela and Colombia have reported levels between 1.7 and 15.7% (Arjona-Jiménez et al 2012, 5.6 and 40.0%, (Zerpa et al 2000, 2001, Feliciangeli et al 2005) and 1.6 and 36.0% (Fernández et al 2002, Cortés 2006, Rosypal et al 2007, Paternina-Gómez et al 2013, respectively [EB1].…”
Section: Canine Visceral Leishmaniosismentioning
confidence: 99%